Ownership Of Residential House For Foreigners Based On Agreement - Istri Agung, Anak Agung (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Decree of the Minister of Agrarian and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 1241/SK-HK.02/IX/2022 on the Acquisition and Price of Residential Houses for Foreigners, as one of the drivers of investment in Indonesia. However, the certainty of the form and type of agreement that must be made for foreigners is unclear in its regulation, so many make nominee agreements and cause conflicts and even disputes in court. On the one hand, there are restrictions for foreigners, and on the other hand, the opening of the broadest possible opportunity for the entry of foreign investment in Indonesia. The form of Agreement of Ownership of a Residential House for Foreigners can be made with a deed under the hand or with an authentic deed, however, made authentically with a notarial deed or PPAT provides more legal certainty, because of the perfect evidentiary power. In order to fulfill legal certainty, the type of agreement that can be made is in the form of sale and purchase of use rights to land and buildings as well as leasing rights to land and buildings, and sale and purchase agreements of Sarusun or Sarusun property rights. In addition, for PMA Legal Entities can have HGB. The Decree of the Minister of Agrarian and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number: 1241/SK-HK.02/IX/2022 has provided legal certainty and a sense of justice for all people and for foreigners whose presence in Indonesia in accordance with applicable regulations provides benefits, conducts business, works or invests in Indonesia by heeding existing regulations so that it has an impact on the welfare of the community, nation, state and foreigners/foreign investors in Indonesia.